Subcutaneous Emphysema after a Dental Procedure - Brito, Daniela; Medeiros, Catarina; Caley, Lidia (European Journal of Case Reports in Internal Medicine, 2022)
Subcutaneous emphysema is the presence of air beneath the skin’s soft tissues. It can result from medical conditions, trauma or iatrogenic causes. The occurrence of subcutaneous emphysema after a dental procedure is rare. Although it is mostly a benign and self-limiting complication, the consequences may be severe and life-threatening. We report the case of a 20-year-old man who presented to the emergency department with swelling of his face and neck after dental treatment. The diagnosis of subcutaneous emphysema and pneumomediastinum was made based on physical examination and a computerized tomography scan.